Meningkatkan Kesadaran Identitas Rumah dan Kebersihan Lingkungan Melalui Program Pembuatan Nomor Rumah dan Bak Sampah Di Dusun Patoksari, Desa Plaosan, Kabupaten Malang - Sesoca, Jendra; Harianto, Dani; Meo, Maxima; Kapoteng, Penina; Syah, Arizky Syafrial (Abdimas Indonesian Journal, 2025)
KKN (Real Work Lecture) activities aim to apply the scientific knowledge that students gain during their studies in the community and as a forum for community service. Making house numbers and trash cans is one of the work programs carried out by Regular KKN students at Wisnuwardhana University Malang located in Patuksari Hamlet, Plaosan Village. Based on the survey results, most of the residents' houses in Patuksari Hamlet do not have house numbers and there are no trash bins for storing waste. So village officials who want to collect data and senders of goods also have difficulty finding home addresses. Apart from that, many people throw their household waste into areas around the river. Therefore, Regular KKN students at Wisnuwardhana University Malang created this program, by installing 80 house numbers consisting of 40 house numbers for RT 02 and 40 numbers for RT 04 with 2 trash bins for each RT consisting of organic and non-organic waste bins.